Understanding Cultural Intelligence Factors among Business Students in Romania. (7th June 2016) - Brancu, Laura; Munteanu, Valentin; Golet, Ionut
Abstract: Cultural intelligence (CQ) is a relatively new concept, one that explains why certain individuals can adapt to different cultural contexts more efficiently than others. Using Earley & Ang's (2003) multidimensional concept as an analysis framework, this paper will study the intercultural intelligence among business students in Romania. We have chosen this research topic because we believe that the business students of today will become the global managers of tomorrow. Given that CQ is a multidimensional concept, this paper will analyze the answers for each of the four CQ dimensions, in order to identify which of the four capabilities is more or less developed among students. The final purpose is to understand the CQ components on which higher education should focus more. We wish to find educational solutions adapted to the actual needs of business graduates.